1968
DOI: 10.1113/jphysiol.1968.sp008456
|View full text |Cite
|
Sign up to set email alerts
|

Effect on temperature of 5‐hydroxytryptamine injected into the cerebral ventricles of cats

Abstract: SUMMARY1. In unanaesthetized cats the effect on rectal temperature was examined of 5-HT injected through a Collison cannula chronically implanted into the left lateral ventricle. The response depended on the amount of 5-HT injected and on the solvent employed.2. An intraventricular injection of 200 ,ug 5-HT creatinine sulphate dissolved in 0 9 % NaCl solution resulted in a long-lasting rise often interrupted initially by a transient fall in temperature.3. This fall became more prominent with larger doses of 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1969
1969
1978
1978

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The volumes of solution injected exceed the entire dimensions of the anterior hypothalamus, or a sufficiently large dose of the substance applied directly into the diencephalic tissue causes a transient fall in temperature simply because of a depolarizing blockade of the thermosensitive neurons in the rat's hypothalamus (Satinoff, 1964). A similar type of transient synaptic inhibition may also account for the short-lived decline in temperature following an intracerebral injection of a large dose of 5-HT in the monkey and other species (Banerjee, Burks & Feldberg, 1968). Since the characteristics of the release of ACh in the present experiments demonstrate that this amine is devoted principally to the heat production mechanism, it would appear that different experimental procedures are required to determine the role of ACh in the temperature-sensor, heat-production pathway in species with smaller cerebral dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…The volumes of solution injected exceed the entire dimensions of the anterior hypothalamus, or a sufficiently large dose of the substance applied directly into the diencephalic tissue causes a transient fall in temperature simply because of a depolarizing blockade of the thermosensitive neurons in the rat's hypothalamus (Satinoff, 1964). A similar type of transient synaptic inhibition may also account for the short-lived decline in temperature following an intracerebral injection of a large dose of 5-HT in the monkey and other species (Banerjee, Burks & Feldberg, 1968). Since the characteristics of the release of ACh in the present experiments demonstrate that this amine is devoted principally to the heat production mechanism, it would appear that different experimental procedures are required to determine the role of ACh in the temperature-sensor, heat-production pathway in species with smaller cerebral dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…However, Myers (1968) has suggested that high doses of 5-HT may cause a synaptic block in the monkey. Such a block might also account for the biphasic responses to 5-HT which sometimes occurred in the cat (Banerjee et al 1968) and the discrepancies in the reported effects of 5-HT on the body temperature of the cat (Feldberg & Myers, 1963;Kulkarni, 1967).…”
Section: Central Transmitters and Thermoregulation 389mentioning
confidence: 99%
“…Thus, * Beit Memorial Research Fellow. M. A. SIMMONDS in the cat, dog and monkey, 5-HT causes a rise in temperature (Feldberg & Myers, 1965; Ruckebusch, Grivel & Laplace, 1965;Feldberg, Hellon & Lotti, 1967;Banerjee, Burks & Feldberg, 1968) while, in the rat, mouse, rabbit, ox and sheep, a fall in temperature is observed (Cooper, Cranston & Honour, 1965;Brittain & Handley, 1967;Feldberg & Lotti, 1967;Findlay & Thompson, 1968;Myers & Yaksh, 1968;Bligh & Cottle, 1969).…”
Section: Introductionmentioning
confidence: 99%